ANALYSIS OF THE INFLUENCE OF PERCEIVED VALUE, PERCEIVED QUALITY, AND BRAND EXPERIENCE ON BRAND LOYALTY IN THE ELECTRIC CIGARETTE INDUSTRY - Melva Hermayanty Saragih; Afif Audric Putera Jaya (Suluh Adiluhung Publisher (SAPub), 2026)
According to the Indonesian Youth Council for Tobacco Control (IYCTC, 2022), Indonesia is predicted to have the largest market share for e-cigarettes, specifically vapes, in Southeast Asia. Over the past decade, the e-cigarette industry has emerged as one of the fastest growing segments in the tobacco industry. This study aims to analyze the influence of perceived value, perceived quality, and brand experience on brand loyalty among e-cigarette consumers in Semarang. The study employed a quantitative approach; with data collection conducted through a questionnaire measured using a 5-point Likert scale. The sampling technique used probability sampling, resulting in a total of 102 items. The data was analyzed using multiple regression analysis with SPSS. The results indicate that perceived value, perceived quality, and brand experience have a significant influence on brand loyalty. The results also indicate that perceived quality has the greatest influence on brand loyalty.